2013
DOI: 10.1177/1555412013493133
|View full text |Cite
|
Sign up to set email alerts
|

The Morality of Play

Abstract: Over the last several decades, video games have become one of America's most popular pastimes. Sadly, little academic work has studied media coverage of video games during this transformation. Williams' analysis of news magazines' coverage from 1970 to 2000 offers the only research into this topic. However, the video game industry has significantly changed since 2000. To remedy this gap, I examine video game coverage in The New York Times over the last three decades. During this period, evaluative articles pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…As a result concerns regarding the consequences of exposure to violent content, such as associated aggression following playing with violent games (American Psychological Association [APA], 2015). The media in the 1990s started to portray video games as a threat due to vulnerable children and adolescents having access to and playing early video games (McKernan, 2013). The frequent use of excessive violence in video games has become controversial and as such became the focus of research for the next 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…As a result concerns regarding the consequences of exposure to violent content, such as associated aggression following playing with violent games (American Psychological Association [APA], 2015). The media in the 1990s started to portray video games as a threat due to vulnerable children and adolescents having access to and playing early video games (McKernan, 2013). The frequent use of excessive violence in video games has become controversial and as such became the focus of research for the next 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…University students were suggested not to have relationships between video game play and moral development, compared to previous research with adolescents which did suggest a relationship with moral development (Bajovic, 2013;Hodge et al, 2019). Therefore, demonstrating the importance and value of these rating boards for younger audiences; as it was the younger audience which lead to concerns and controversy for video games and lead to the introduction of these systems (McKernan, 2013). This lack of relationship between moral development and video game play for adults; supports the appropriateness of the age ratings to be for those aged under 18 as those over 18 could be less susceptible to influences from the content and guidance is not needed.…”
Section: Discussionmentioning
confidence: 97%
“…In light of this, the aim of this explorative study is to question whether this aim is achieved. However, given that, there is little academic work dealing with the media’s coverage of video games (McKernan, 2013), no comparable German study could be identified to highlight the study’s significance. Instead, the study sets out to provide an empirical quantitative study on how German public television covers video games.…”
Section: Introductionmentioning
confidence: 99%